Morfometrik Ikan Cere (Gambusia affinis) dan Ikan Putian (Rasbora argyrotaeni) yang Terpapar Merkuri di Sungai Tambang Saweak Kabupaten Lebong - Deka Agustina; Aceng Ruyani; Euis Nursa’adah (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Mercury (Hg) is a pollutant that is dangerous because it is toxic when it accumulates in living tissue and is difficult to decompose in the environment, if it is polluted it will be very dangerous for the environment and living things around it. In this study the aim was to determine the mercury content of the morphometrics of fish in the Selikat River, Tambang Saweak Village. Based on the results of the study, it was found that 2 species of fish were exposed to mercury and not exposed, namely Cere fish (Gambusia affinis) exposed to mercury of 0.47 mg/Kg and Putian fish (Rasbora argyrotaenia) exposed to mercury of 0.43 mg/Kg. Where in the two fish there are morphometric differences, namely differences in body height (TB), tail stem height (TBE), dorsal fin length (PDO) and anal fin length (PA). This happens because fish that are exposed to toxic compounds or heavy metals such as mercury (Hg) can experience tissue damage and affect the body size and body shape of the fish. If fish exposed to mercury are eaten by humans, it will have consequences for human health such as poisoning and can cause ataxia, decreased speech and hearing ability, tremors, dysarthria and ultimately death.